2018
DOI: 10.15171/apb.2018.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cucurbita Maxima on Control of Blood Glucose in Diabetic Critically Ill Patients

Abstract: Purpose: Cucurbita maxima Duchense (C. maxima) has been widely used in China and Mexico as a hypoglycemic plant for controlling blood glucose in diabetic patients. Furthermore, in northwest of Iran, this plant is used traditionally for controlling of diabetes. We examined the effect of C. maxima pulp besides insulin on control of hyperglycemia in diabetic patients admitted to Intensive care unit (ICU).Methods: Twenty critically ill patients who were admitted to the ICU were enrolled in this study. 5g lyophiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…Mahmoodpoor et al [106] in a recent study performed on patients with severe diabetes from the Intensive Care Unit showed the hypoglycemic effect of C. maxima pulp. The subjects received five grams of C. maxima powder per 12 h for three consecutive days.…”
Section: Clinical Effectiveness Of Cucurbita Plants In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Mahmoodpoor et al [106] in a recent study performed on patients with severe diabetes from the Intensive Care Unit showed the hypoglycemic effect of C. maxima pulp. The subjects received five grams of C. maxima powder per 12 h for three consecutive days.…”
Section: Clinical Effectiveness Of Cucurbita Plants In Humansmentioning
confidence: 99%
“…The subjects received five grams of C. maxima powder per 12 h for three consecutive days. After the treatment, it was observed a decrease of serum glucose levels from 214.9 mg/dL to 214.9 mg/dL associated with a reduction of insulin doses from 48.05 IU to 39.5 IU [106]. C. ficifolia also showed a good hypoglycemic effect when the extract was administered in doses of 4 mL/kg to patients with type 2 diabetes and moderately elevated blood glucose level [105].…”
Section: Clinical Effectiveness Of Cucurbita Plants In Humansmentioning
confidence: 99%
“…Especially important, given the high NCD (particularly diabetes) rates in the Pacific and northern Australia, are the anti-diabetes and anti-cardiovascular disease effects of most of the plants featured in the factsheets, demonstrated in scientific studies. Studies with evidence for this include the following: drumstick [ 36 , 37 , 38 , 50 , 60 ], amaranth [ 61 , 62 , 63 ], bele [ 64 , 65 , 66 ], chilli [ 67 , 68 , 69 ], purslane [ 70 , 71 , 72 ], kangkong [ 73 , 74 , 75 ], ofenga [ 76 , 77 , 78 ], hedge panax [ 79 , 80 ], chaya [ 39 , 40 ], pumpkin [ 81 , 82 ], and choko [ 83 , 84 ]. Their inclusion in the diet in sufficient quantity is likely to reduce the risk of diabetes and cardiovascular disease, not only by reducing glycemic load when they are included with high-carbohydrate meals, but also because of specific anti-diabetes effects.…”
Section: Resultsmentioning
confidence: 99%
“…Os efeitos hipoglicêmicos de Cucurbita máxima foram encontrados tanto na polpa quanto nas sementes das abóboras, delineada como benéficas para ratos diabéticos e pacientes portadores de Diabetes Mellitus Tipo II. Quando comparadas as espécies, é evidenciado que a C. máxima e C. moschata possui ativos antidiabéticos relevantes para a literatura, passando ser frequente o seu uso (MAHMOODPOOR et al, 2018).…”
Section: Introductionunclassified
“…A Cucurbita máxima também conhecida como moranga, possui caule suculento e flexível, sendo documentado nas folhas características trifolioladas, alternas e pendúculos (MAHMOODPOOR et al, 2018). Em um estudo experimental Mahmoodpoor et al (2018) examinou o efeito da polpa de C. máxima em pacientes diabéticos internados na UTI com análise dos níveis de insulina e glicemia, após administração de cinco gramas de pó liofilizado de C. máxima a cada 12 horas por três dias. Os resultados obtidos foram satisfatórios com diminuição dos níveis elevados de glicose no sangue de maneira rápida e eficaz nos pacientes diabéticos em estado crítico.…”
Section: Introductionunclassified